Factors associated with self-reported capacity to walk, jog and run in individuals with systemic lupus erythematosus - Gizem İrem KINIKLI,; Susanne PETTERSSON,; Sevilay KARAHAN,; Iva GUNNARSSON,; Elisabet SVENUNGSSON,; Carina BOSTRÖM, (Archives of Rheumatology, 2021)
Objectives: This study aims to explore how disease and health-related quality of life (HRQOL) factors are associated with self-reported physical capacity in walking, jogging and running in systemic lupus erythematosus (SLE). Patients and methods: This cross-sectional study is part of an ongoing cohort research project which started in 2014. A total of 198 patients (21 males, 177 females; mean age 51.5±16.1 years; range, 20 to 82 years) with SLE answered a question concerning physical capacity and the answers were categorized as low (can walk less than 2 km) and high (can jog and run at least 2 km) capacity. Additional measurements of disease activity (Systemic Lupus Activity Measure-Revised, SLAM-R), organ damage (Systemic Lupus International Collaborating Clinics-Damage Index, SLICC-DI), physical activity (International Physical Activity Questionnaire-Short Form, IPAQ-SF), exercise during the past year, Hospital Anxiety and Depression Scale (HADS), and HRQOL according to EuroQol five-dimension score and EuroQol visual analog scale (EQ-VAS) were included. The independent variables in the multiple logistic regression analysis were age, body mass index (BMI), disease duration, SLAM-R, SLICC-DI, IPAQ-SF category, sitting hours (IPAQ-SF), and exercise during the past year as well as HADS and EQ-VAS. Results: Patients that reported low physical capacity (n=120) were older (p<0.001), had longer disease duration (p<0.001), had more organ damage (p<0.001), reported that they were less physically active (p=0.003), exercised less during the past year (p=0.001), reported more pain/discomfort and depressive symptom (p<0.001) and had lower overall HRQOL (p<0.001) and mobility and usual activities than those that reported high capacity (n=78). The regression analysis showed that age (median ≤49 vs >49) (Exp) (B): 4.52 (95% confidence interval [CI]: 2.05 to 9.98) (p<0.001), disease duration (median ≤17 vs >17) Exp (B): 2.53 (95% CI: 1.15 to 5.60) (p=0.02), SLICC-DI (median <1 vs ≥1) Exp (B): 3.60 (95% CI: 1.48 to 8.73) (p=0.005), and EQ-VAS (median <72 vs ≥72) Exp (B): 4.63 (95% CI: 2.13 to 10.05) (p<0.001) were significant factors associated with physical capacity (Nagelkerke R Squared=0.46). Conclusion: Patients with low physical capacity were less physically active, exercised less and had more pain and depressive symptoms than those that reported a high capacity. However, only age, disease duration, organ damage and overall HRQOL were indicators of low physical capacity. In order to increase physical capacity in the management of SLE, it is important to address overall HRQOL.